Left Atrial Appendage Occlusion as an Alternative to Anticoagulation - Ibrahim Akin; Christian Fastner; Christoph A. Nienaber (Highlights on Medicine and Medical Research Vol. 12, 2021)
Non-valvular atrial fibrillation is associated with a significantly increased risk of embolic stroke as a result of blood clots forming primarily in the left atrial appendage (LAA). Permanent administration of anticoagulants or interventional LAA occlusion are two preventive measures to avoid embolic events. In the past, physical LAA occlusion required either surgical excision or exclusion by suture or stapler. Nowadays, various clinical trials provide evidence about safety, effectiveness and therapeutic success of LAA occlusion using various interventional occluder devices. As the safety, clinical benefit, and cost-effectiveness of LAA occlusion have been demonstrated, the use of such implants has become a valuable alternative for stroke prevention in patients with contraindications to anticoagulation.